Explorando a acústica das abelhas vibradoras como indicador da diversidade de abelhas e da eficiência da polinização em flores poricidas - Arvelos, César Augusto (2023)
Biodiversity plays a fundamental role in ecosystems, with each species can contribute uniquely to their healthy functioning. However, as diversity is often measured through species count and abundance, indirect methods like acoustic analysis can offer an alternative approach to studying communities and the role of species in ecosystem functioning. Among animals that emit sounds in the environment, bees, despite being relatively understudied in this context, are an important group. Vibrating bees stand out for producing distinct sounds between species during their interactions with plants. Since the sounds produced during floral vibration by these bees are linked to their morphological attributes, the acoustic diversity of vibrations can influence the reproductive success of plants. In this study, we investigated the relationship between the acoustic characteristics of vibrating bees, the diversity of visiting species, and plant male performance. For this purpose, we observed and recorded bee visits in a population of Rhynchanthera grandiflora. We concatenated the visit sounds, calculated acoustic indices, and examined their associations with bee diversity and the amount of pollen released from the anthers. The acoustic indices of Acoustic Evenness Index (AEI), Acoustic Diversity Index (ADI), and Bioacoustic Index (BIO) proved to be the best predictors of bee diversity; however, we believe they better predict functional diversity than species diversity. In summary, this study highlights the utility of vibrational characteristics of vibrating bees in assessing functional diversity within the community and its effect on R. grandiflora pollination. It also emphasizes the differential effect of complementarity and functional redundancy depending on the number of visits. In scenarios with few visits, functional complementarity enhances male performance, while redundancy positively affects this performance in situations with an abundance of visiting bees.